Seeing like a state : how certain schemes to improve the human condition have failed - Scott, James C. (Yale University Press, 2020)
"Hailed as 'a magisterial critique of top-down social planning' by the New York Times, this essential work analyzes disasters from Russia to Tanzania to uncover why states so often fail--sometimes catastrophically--in grand efforts to engineer their society or their environment, and uncovers the conditions common to all such planning disasters."--Provided by publisher